Pandemic Implication on Muslim Women Religiosity : (Multi Sites Studies in Australia, Malaysia and Indonesia) - Irfan Yuhadi; Nurul Budi Murtini; Teguh Dwi Cahyadi (Jurnal Al-Fawa'id : Jurnal Agama dan Bahasa, 2023)
The purpose of this research is to find phenomena, positive implications and negative implications of the Covid-19 pandemic on Muslim women religiosity. Allah, the Exalted and Glorious, tests men with a touch of fear, loss of property, and death. Among the forms of testing for men is the presence of disease plague. Corona virus disease (Covid-19) began to spread in Wuhan China in December 2019. Covid-19 is now a pandemic that occurs in many countries around the world. Australia is a country in the southern hemisphere consisting of the mainland of the Australian continent, the island of Tasmania and various small islands in the Indian Ocean and Pacific Ocean. Malaysia is a federal state in Southeast Asia. Indonesia is the largest archipelago country in the world and the country with the largest Muslim population in the world. The researcher chose three countries to get comprehensive results about the problem formulation in this study. The religiosity of a Muslim woman is the extent to which a Muslim woman adheres to religious values in her beliefs and practices in everyday life. The approach in this research was use a qualitative approach with the research type of case study and the design of this research is multi sites in three countries; Australia, Malaysia and Indonesia. The data were collected by using purposive sampling from key informants and snowball sampling. The result of this study indicates that: (1) There is a similar phenomenon of the Covid-19 pandemic that occurred in Australia, Malaysia and Indonesia. (2) The positive implications of the Covid-19 pandemic on the religiosity of Muslim women are on the sides: external individual religiosity, inner individual religiosity, and religiosity for social benefits. (3) The negative implication of the Covid-19 pandemic on Muslim women religiosity is on the side of religiosity which is direct-encounter and has the potential to cause crowds.